Diaphragm, preparation method thereof, secondary battery and device
By using a flame retardant layer containing a specific flame retardant composition in the separator of the lithium-ion battery, the problem of thermal runaway in the abnormal state is solved, and higher safety performance is achieved.
Patent Information
- Application Number
- CN202311181936.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
Existing lithium-ion batteries are prone to internal short circuits under abnormal conditions such as overcharge, high temperature or needle puncture, resulting in thermal runaway. The existing modified diaphragms cannot effectively block the contact between the aluminum foil burrs and the negative electrode sheet, and cannot effectively avoid thermal runaway.
A diaphragm including a base film and a flame retardant layer is used. The flame retardant composition used in the flame retardant layer includes components such as urea phosphate, a mixture of phosphoric acid and urea, dihydroamine phosphate and diamine phosphate, which can be thermally expanded at a lower temperature to avoid contact between the positive electrode sheet and the negative electrode sheet.
By increasing the short-circuit resistance of the diaphragm and reducing the short-circuit current, the generation of ohmic heat is effectively improved, and the occurrence of thermal runaway is avoided.
Smart Images

Figure CN119627368A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage, and specifically provides a diaphragm and a preparation method thereof, a secondary battery and a device. Background Art
[0002] With the development of the new energy vehicle industry, higher expectations are placed on the energy density of lithium-ion batteries. At present, the improvement of energy density is mainly focused on the improvement of positive electrode materials or negative electrode materials, such as the use of NCM (nickel cobalt manganese) positive electrode or graphite doped silicon negative electrode to improve the energy density of the battery. However, with the continuous improvement of energy density, the shortcomings in battery safety performance limit the development of high energy density batteries.
[0003] When the battery is in abnormal conditions such as overcharge, high temperature, and penetration, an internal short circuit occurs between the positive and negative electrodes, generating ohmic heat, accompanied by chemical reaction heat. The heat inside the battery continues to accumulate until the internal temperature exceeds 300°C. At this time, the positive electrode begins to release highly active oxygen, which further causes serious redox reactions of combustible materials in the battery, ultimately leading to uncontrollable thermal runaway of the lithium-ion battery.
[0004] Therefore, current secondary batteries and devices still need to be improved. Summary of the invention
[0005] At present, the defense against battery thermal runaway is mainly focused on PACK (battery pack) and BMS (battery management system). In the prior art, in order to improve the safety performance of the diaphragm, high-heat-resistant ceramics or high-heat-resistant polymers such as aramid are usually coated on the surface of the diaphragm to improve its thermal shrinkage performance at high temperatures. However, when the battery faces an internal short circuit caused by acupuncture, the aluminum foil burrs in the positive electrode plate often come into contact with the charged negative electrode plate, thereby causing thermal runaway. The current modified diaphragm cannot block the contact between the aluminum foil burrs and the negative electrode plate during the acupuncture process, and prevent the internal short circuit from causing a series of ohmic heat, chemical heat and combustion heat, and thus cannot effectively prevent the battery from thermal runaway. Therefore, this field needs to improve the safety performance of the battery from the inside, especially the diaphragm.
[0006] In order to solve at least one of the above problems to a certain extent, the present invention provides a diaphragm, which includes a flame retardant layer disposed on a base film, and the flame retardant composition in the flame retardant layer includes a first component, wherein the first component includes: (i) urea phosphate, (ii) a mixture of phosphoric acid and urea, (iii) diammonium phosphate and (iv) diammonium hydrogen phosphate. The expansion temperature of a conventional intumescent flame retardant is generally between 250°C and 300°C, at which the battery cell has already undergone thermal runaway, and thus the conventional intumescent flame retardant cannot guarantee the acupuncture safety of the battery cell. Compared with conventional intumescent flame retardants, the first component used in the diaphragm according to the present invention can be thermally expanded at a lower temperature (e.g., 150°C to 200°C) during the acupuncture process, thereby avoiding the contact between the burrs of the positive electrode sheet (e.g., the positive electrode current collector, such as aluminum foil) near the steel needle and the negative electrode sheet, which is beneficial to increase the short-circuit resistance and reduce the short-circuit current, reduce the generation of ohmic heat, and ultimately effectively improve the acupuncture safety of the battery cell. Therefore, when the internal temperature of the battery cell using the separator rises, the flame retardant layer rapidly expands dozens of times due to the first component, thereby quickly separating the positive electrode collector such as aluminum foil and the negative electrode plate, avoiding the occurrence of needle puncture short circuit.
[0007] The object of the present invention is to provide a diaphragm, which comprises: a base film; a flame retardant layer, wherein the flame retardant layer is arranged on the base film, the flame retardant layer comprises a flame retardant composition, and the flame retardant composition comprises a first component, wherein the first component comprises: at least one of (i) urea phosphate, (ii) a mixture of phosphoric acid and urea, (iii) diammonium phosphate and (iv) diammonium hydrogen phosphate.
[0008] The present invention also aims to provide a method for preparing a diaphragm, which method comprises: providing a base film and a flame retardant layer slurry, wherein the flame retardant layer slurry comprises a flame retardant composition, wherein the flame retardant composition comprises a first component, wherein the first component comprises: at least one of (i) urea phosphate, (ii) a mixture of phosphoric acid and urea, (iii) diammonium phosphate and (iv) diammonium hydrogen phosphate; forming the flame retardant layer slurry on the base film, and forming the diaphragm by drying.
[0009] Another object of the present invention is to provide a secondary battery, which comprises a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator according to the present invention or a separator formed by the preparation method according to the present invention.
[0010] Another object of the present invention is to provide a device, which comprises the secondary battery according to the present invention.
[0011] Compared with the traditional solution, the present invention has the following beneficial effects:
[0012] Compared with the traditional intumescent flame retardant, when the separator according to the present invention is used for the battery core, the first component of the flame retardant composition used in the separator can be thermally expanded at a lower temperature (e.g., 150°C to 200°C) during the needling process, thereby avoiding the contact between the positive electrode active material or the positive electrode current collector burr near the steel needle and the negative electrode active material during the needling process. Therefore, the addition of the first component can increase the short-circuit resistance of the separator and reduce the short-circuit current, thereby reducing the generation of ohmic heat, and ultimately effectively improving the needling safety of the battery core using the separator. Therefore, when the internal temperature of the battery core using the separator rises, the flame retardant layer rapidly expands dozens of times due to the first component, thereby quickly separating the positive electrode current collector such as aluminum foil and the negative electrode plate, avoiding the generation of needling short circuits. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to make the above-mentioned purpose, features and advantages of the present invention easier to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein, so the present invention is not limited to the specific embodiments disclosed below.
[0014] Figure 1 The schematic diagram of the structure of the diaphragm coated with a flame retardant layer on one side according to the present invention is shown;
[0015] Figure 2 The schematic diagram of the structure of the diaphragm coated with flame retardant layers on both sides according to the present invention is shown;
[0016] Figure 3 The schematic diagram of the structure of the flame retardant layer expanding when the diaphragm according to the present invention is punctured by a needle is shown.
[0017] Reference numerals
[0018] 100: base film; 200: flame retardant layer; 300: positive electrode active material layer; 400: positive electrode current collector; 500: expanded carbon layer formed when the flame retardant layer is punctured; 600: negative electrode current collector; 700: negative electrode active material layer. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described in conjunction with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present invention. The embodiments of the present invention should not be interpreted as limiting the present invention. All other embodiments obtained by those skilled in the art based on the technical scheme provided by the present invention and the embodiments given belong to the scope of protection of the present invention.
[0020] Unless otherwise specified, the terms used in the present invention have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in the present invention can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of the present invention).
[0021] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0022] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0023] 1. Diaphragm
[0024] In a first aspect, the present invention provides a diaphragm, comprising: a base film and a flame retardant layer, the flame retardant layer being arranged on the base film, the flame retardant layer comprising a flame retardant composition, the flame retardant composition comprising a first component, the first component comprising: at least one of (i) urea phosphate, (ii) a mixture of phosphoric acid and urea, (iii) diammonium phosphate and (iv) diammonium hydrogen phosphate. Thus, when the diaphragm is used for a battery cell, the first component of the flame retardant composition used in the diaphragm can be thermally expanded at a lower temperature (e.g., 150°C to 200°C) during the acupuncture process, thereby avoiding the contact between the positive active material or the positive current collector burr near the steel needle and the negative active material during the acupuncture process, thereby the addition of the first component can increase the short-circuit resistance of the diaphragm and reduce the short-circuit current, thereby reducing the generation of ohmic heat, and finally effectively improving the acupuncture safety of the battery cell using the diaphragm. Therefore, when the internal temperature of the battery cell using the separator rises, the flame retardant layer rapidly expands dozens of times due to the first component, thereby quickly separating the positive electrode collector such as aluminum foil and the negative electrode plate, avoiding the occurrence of needle puncture short circuit.
[0025] According to one embodiment of the present invention, the first component includes at least one of urea phosphate, diammonium phosphate and diammonium hydrogen phosphate.
[0026] According to one embodiment of the present invention, the flame retardant composition further comprises: a second component, a third component and a fourth component. The second component comprises at least one of ammonium polyphosphate, phosphate, sodium tetraborate and ammonium borate. The second component can release inorganic acid under heating conditions. The third component comprises at least one of pentaerythritol, dipentaerythritol, tripentaerythritol, phenolic resin, polyamide, butanethrol, cyclohexane hexol, starch, maltose, piperazine pyrophosphate and triazine compounds. The third component is a carbon-rich multifunctional (such as hydroxyl) material that can form a foamed carbon layer. The fourth component comprises at least one of melamine, urea, dicyandiamide, urea-formaldehyde resin and polyurea. The fourth component can release inert gas when heated. Therefore, when the battery cell using the diaphragm is heated, the first component in the flame retardant layer decomposes to produce phosphoric acid and forms a porous and closed-structured foam-like expanded carbon layer with the second component (such as ammonium polyphosphate), the third component (such as pentaerythritol) and the fourth component (such as melamine) under high temperature, thereby weakening the diffusion of combustibles and oxygen. At the same time, the fourth component releases NH3 non-combustible gas, continuously diluting the oxygen released by the positive electrode and the oxygen in the air. The expanded carbon layer itself is non-combustible and expands under the action of the gas to block the combustion of oxygen and combustibles, increase the short-circuit resistance and reduce the short-circuit current. With the help of the flame retardant layer of the present invention, the self-extinguishing time of the battery cell combustion can be greatly shortened, thereby effectively improving the safety performance of the battery. Specifically, refer to Figure 3 The separator of the present invention is arranged between a positive electrode sheet coated on both sides (including a positive electrode current collector 400 and a positive electrode active material layer coated on both sides 300) and a negative electrode sheet (including a negative electrode current collector 600 and a negative electrode active material layer coated on both sides 700). When the battery cell using the separator is subjected to high temperature (for example, greater than or equal to 150° C.) and / or acupuncture, the first component in the flame retardant layer of the separator can decompose to produce phosphoric acid and react with the second component (for example, ammonium polyphosphate), the third component (for example, pentaerythritol) and the fourth component (for example, melamine) at high temperature. A porous and closed-structured foam-like expanded carbon layer 500 is formed at a temperature (for example, greater than or equal to 150°C) to weaken the diffusion of combustibles and oxygen. At the same time, the fourth component releases NH3 non-combustible gas, continuously diluting the oxygen released by the positive electrode and the oxygen in the air. The expanded carbon layer 500 itself is non-combustible and expands under the action of the gas to block the combustion of oxygen and combustibles, increase the short-circuit resistance and reduce the short-circuit current. With the help of the flame-retardant layer according to the present invention, the self-extinguishing time of the battery cell combustion can be greatly shortened, thereby effectively improving the safety performance of the battery.
[0027] According to one embodiment of the present invention, the flame retardant composition consists of a first component, a second component, a third component and a fourth component.
[0028] According to one embodiment of the present invention, the base film includes at least one of polyethylene, polypropylene, polypropylene / polyethylene / polypropylene three-layer composite film, polyethylene terephthalate, polyimide and aramid. According to one embodiment of the present invention, the thickness of the base film is 5μm to 20μm. In some embodiments, the thickness of the base film is 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or any value therebetween. In some embodiments, the thickness of the base film is 5μm to 15μm.
[0029] The thickness of the flame retardant layer is 1 μm to 20 μm. In some embodiments, the thickness of the flame retardant layer is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm or any value therebetween. In some embodiments, the thickness of the flame retardant layer is 1 μm to 10 μm.
[0030] According to one embodiment of the present invention, based on the total mass of the flame retardant layer, the mass percentage of the flame retardant composition is 57% to 93%. In some embodiments, based on the total mass of the flame retardant layer, the mass percentage of the flame retardant composition is 57%, 58%, 59%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 91%, 92%, 93% or any value therebetween. As a result, the flame retardant layer can expand at a temperature of 150°C, thereby preventing thermal runaway of the battery cell; when the content of the flame retardant composition is too high, the stability of the flame retardant layer is poor; when the content of the flame retardant composition is too low, the flame retardant effect of the flame retardant layer is poor.
[0031] According to one embodiment of the present invention, based on the total mass of the flame retardant composition, the mass percentage of the first component is 2% to 5%, the mass percentage of the second component is 55% to 68%, the mass percentage of the third component is 15% to 20%, and the mass percentage of the fourth component is 15% to 20%. In some embodiments, based on the total mass of the flame retardant composition, the mass percentage of the first component is 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any value therebetween, the mass percentage of the second component is 55%, 57%, 59%, 60%, 62%, 64%, 66%, 68% or any value therebetween, the mass percentage of the third component is 15%, 16%, 17%, 18%, 19%, 20% or any value therebetween, and the mass percentage of the fourth component is 15%, 16%, 17%, 18%, 19%, 20% or any value therebetween. Thus, with the help of the appropriate content of the first component, the foaming temperature of the flame retardant layer can be reduced. For example, during the drying process of the flame retardant layer, the first component will recrystallize. When the content of the first component is too high, for example, higher than 5%, the slurry will have a noticeable granular feel, the slurry has poor film-forming properties, and the coating surface will crack significantly, thereby affecting the coating process; when the first component is too low, it cannot effectively reduce the foaming temperature.
[0032] According to one embodiment of the present invention, the flame retardant layer further comprises: first inorganic particles, the first inorganic particles comprising at least one of aluminum oxide, boehmite, magnesium hydroxide, aluminum hydroxide, garnet and silicon dioxide; based on the total mass of the flame retardant layer, the mass percentage of the first inorganic particles is 5% to 40%. In some embodiments, based on the total mass of the flame retardant layer, the mass percentage of the first inorganic particles is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any value therebetween.
[0033] According to one embodiment of the present invention, the flame retardant layer further comprises: a first binder, the first binder comprising at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylate, polyvinyl alcohol and polyvinylidene fluoride; based on the total mass of the flame retardant layer, the mass percentage of the first binder is 2% to 10%. In some embodiments, based on the total mass of the flame retardant layer, the mass percentage of the first binder is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween.
[0034] According to one embodiment of the present invention, the flame retardant layer further comprises: an auxiliary agent, the auxiliary agent comprising at least one of a dispersant, a thickener and a wetting agent; wherein the dispersant comprises at least one selected from polyacrylate, sodium polyacrylate, ammonium polyacrylate, sodium hexametaphosphate, polyethylene glycol, polyethylene glycol ether and polyvinyl pyrrolidone, the thickener comprises at least one selected from sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, gelatin and sodium alginate, and the wetting agent comprises at least one selected from siloxane, polyether-modified polydimethylsiloxane, sodium perfluoroalkyl sulfonate, polyethylene oxide, sodium dodecyl sulfate and sodium dodecyl sulfonate; based on the total mass of the flame retardant layer, the mass percentage of the dispersant is 1% to 2%, the mass percentage of the thickener is 0.3% to 1%, and the mass percentage of the wetting agent is 0.05% to 0.2%. In some embodiments, based on the total mass of the flame retardant composition, the mass percentage of the dispersant is 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any value therebetween, the mass percentage of the thickener is 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any value therebetween, and the mass percentage of the wetting agent is 0.05%, 0.07%, 0.09%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2% or any value therebetween.
[0035] According to one embodiment of the present invention, the flame retardant layer is disposed on one surface of the base film and the surface treatment layer is disposed on the other surface opposite thereto, or the flame retardant layer is disposed on both opposite surfaces of the base film. Figure 1 The flame retardant layer 200 is disposed on one surface of the base film 100 and a surface treatment layer (not shown) is disposed on the other surface of the base film 100. Figure 2 , flame retardant layers 200 are disposed on opposite side surfaces of the base film 100 .
[0036] According to one embodiment of the present invention, the surface treatment layer includes at least one of a combination of a polymer, second inorganic particles, and a second binder.
[0037] According to one embodiment of the present invention, the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl alkoxide, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).
[0038] According to one embodiment of the present invention, in the composition of the second inorganic particles and the second binder, the second inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate, and the second binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0039] The present invention also aims to provide a method for preparing a diaphragm, and the diaphragm prepared by the method may be the diaphragm described above, and thus has all the characteristics and advantages of the diaphragm described above, which will not be repeated here. According to one embodiment of the present invention, the method comprises:
[0040] A base film and a flame retardant layer slurry are provided, wherein the flame retardant layer slurry comprises a flame retardant composition, wherein the flame retardant composition comprises a first component, wherein the first component comprises at least one of (i) urea phosphate, (ii) a mixture of phosphoric acid and urea, (iii) diammonium phosphate, and (iv) diammonium hydrogen phosphate;
[0041] The flame retardant layer slurry is formed on the base film, and the separator is formed by a drying process.
[0042] According to one embodiment of the method of the present invention, the flame retardant composition further comprises a second component, a third component and a fourth component, the second component comprises at least one of ammonium polyphosphate, phosphate, sodium tetraborate and ammonium borate, the third component comprises at least one of pentaerythritol, dipentaerythritol, tripentaerythritol, phenolic resin, polyamide, tetramethylenetetraol, cyclohexane hexol, starch, maltose, piperazine pyrophosphate and triazine compounds, and the fourth component comprises at least one of melamine, urea, dicyandiamide, urea-formaldehyde resin and polyurea. Based on the total mass of the flame retardant composition, the mass percentage of the first component is 2% to 5%, the mass percentage of the second component is 55% to 68%, the mass percentage of the third component is 15% to 20%, and the mass percentage of the fourth component is 15% to 20%.
[0043] According to one embodiment of the method of the present invention, the flame retardant layer slurry further includes first inorganic particles, a first binder and an auxiliary agent, wherein the auxiliary agent includes at least one of a dispersant, a thickener and a wetting agent. The first inorganic particles include at least one of aluminum oxide, boehmite, magnesium hydroxide, aluminum hydroxide, garnet and silicon dioxide, the first binder includes at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylate, polyvinyl alcohol and polyvinylidene fluoride, the dispersant includes at least one of polyacrylate, sodium polyacrylate, ammonium polyacrylate, sodium hexametaphosphate, polyethylene glycol, polyethylene glycol ether and polyvinyl pyrrolidone, the thickener includes at least one of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, gelatin and sodium alginate, and the wetting agent includes at least one of siloxane, polyether-modified polydimethylsiloxane, sodium perfluoroalkyl sulfonate, polyethylene oxide, sodium lauryl sulfate and sodium lauryl sulfonate. Based on the total mass of the flame retardant layer slurry, the mass percentage of the first inorganic particles is 5% to 40%, the mass percentage of the first binder is 2% to 10%, the mass percentage of the dispersant is 1% to 2%, the mass percentage of the thickener is 0.3% to 1%, and the mass percentage of the wetting agent is 0.05% to 0.2%.
[0044] According to one embodiment of the method of the present invention, the flame retardant layer slurry further comprises a solvent, and the solvent comprises water. Specifically, the flame retardant layer slurry can be formed on the base film by a coating method. More specifically, the flame retardant layer slurry can be formed on the base film by a micro-gravure coating method. The temperature of the drying treatment is 100°C to 150°C; and the time is 1h to 5h.
[0045] 2. Secondary battery
[0046] In a second aspect, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and the separator described in the first aspect. The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, and the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material.
[0047] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0048] In some embodiments, the positive electrode active material includes lithium nickel transition metal oxide. In some embodiments, the lithium nickel transition metal oxide includes LiNi x Co y M(1-x-y) At least one of O2, M is selected from at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1. In some embodiments, x is 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or any value therebetween. In some embodiments, y is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or any value therebetween. In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide and lithium nickel manganese oxide. In some embodiments, the positive electrode active material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92, and Ni95.
[0049] In some embodiments, the positive electrode active material layer further includes a binder, which includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0050] In some embodiments, the positive electrode active material layer further includes a conductive agent, which includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0051] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector, such as copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0052] In some embodiments, the negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium. In some embodiments, the silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound, and a silicon carbon compound. In some embodiments, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. In some embodiments, the tin-based material includes at least one of tin, tin oxide, and a tin alloy. In some embodiments, the phosphorus-based material includes phosphorus and / or a phosphorus complex.
[0053] In some embodiments, the negative electrode active material layer also includes a binder, which includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0054] In some embodiments, the negative electrode active material layer further includes a conductive agent, which includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, and a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0055] The secondary battery of the present invention further comprises an electrolyte. The electrolyte that can be used in the present invention can be an electrolyte known in the prior art.
[0056] According to some embodiments of the present invention, the electrolyte includes an organic solvent, a lithium salt and an optional additive. The organic solvent in the electrolyte of the present invention may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present invention is not limited and may be any electrolyte known in the prior art. The additive of the electrolyte according to the present invention may be any additive known in the prior art that can be used as an electrolyte additive.
[0057] According to some embodiments of the present invention, the organic solvent includes at least one of a chain carbonate, a cyclic carbonate and a carboxylate. The chain carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate and a fluorinated chain carbonate. The cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate and butylene carbonate. The carboxylate is selected from at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and a fluorinated carboxylate. In some embodiments, based on the mass of the electrolyte, the mass percentage of the solvent is 40% to 80%. In some embodiments, the mass percentage of the solvent is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In some embodiments, the mass percentage of the solvent is 50%-70%.
[0058] In some embodiments, the lithium salt includes at least one of an organic lithium salt and an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonyl imide (LiTFSI), lithium bis(fluorosulfonyl) imide (LiFSI), lithium bis(oxalate borate) (LiBOB) or lithium difluorooxalate borate (LiDFOB). In some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium salt is 4% to 25%. In some embodiments, the mass percentage of the lithium salt is 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value therebetween. In some embodiments, the mass percentage of the lithium salt is 6% to 18%.
[0059] In some embodiments, the additive includes 1,3-propane sultone (PS), vinyl sulfate (DTD), 1,3-propylene sultone (1,3-PST), vinyl sulfite (ES), tris (trimethylsilyl) phosphate (TMSP), tris (trimethylsilyl) borate (TMSB) and methylene disulfonate (MMDS), succinonitrile, adiponitrile, glutaronitrile, hexane trinitrile, ethyl disulfonic acid ethylene ester, 1-propylene-1,3-sultone (PST), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), ethylene sulfite (DTO), dimethyl sulfite (DMS) and diethyl sulfite (DES) At least one. In some embodiments, based on the mass of the electrolyte, the mass percentage of the additive is 0.05% to 10%. In some embodiments, the mass percentage of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage of the additive is 0.1% to 5%.
[0060] In some embodiments, the method for preparing the secondary battery includes providing an electrode assembly, injecting liquid, packaging and forming. In some embodiments, the temperature of the formation is 40°C to 50°C, for example, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C or 49°C.
[0061] In some embodiments, the formation comprises: charging to 4.25V at 0.05C current and standing for 60min at a temperature of 40°C to 50°C, such as 45°C, and a pressure of 150kgf to 250kgf, such as 210kgf, followed by charging to 4.25V at 0.1C, and then discharging to 3.0V at 0.2C.
[0062] According to some embodiments of the present invention, the secondary battery of the present invention includes, but is not limited to: a lithium ion battery or a sodium ion battery. In some embodiments, the secondary battery is a lithium ion battery. According to some embodiments of the present invention, the secondary battery may include an outer packaging, and the outer packaging may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc. There is no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape.
[0063] 3. Device
[0064] The present invention further provides a device, which comprises the secondary battery described in the second aspect of the present invention.
[0065] The device of the present invention is not particularly limited. In some embodiments, the device of the present invention includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.
[0066] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0067] Examples and Comparative Examples
[0068] Example 1
[0069] Preparation of diaphragm:
[0070] Step 1: The commercially available phosphate particles are ball-milled with a zirconium oxide ball mill, and then the ball-milled ammonium polyphosphate is dispersed in deionized water, centrifuged and vacuum dried to obtain phosphate powder. Step 2: 1.725g of diammonium hydrogen phosphate, 18.975g of phosphate, 6.9g of dipentaerythritol, 6.9g of melamine, 0.75g of polyvinyl pyrrolidone, 0.2g of sodium carboxymethyl cellulose and 0.05g of sodium dodecyl sulfate are fully stirred and dispersed in water, and 3.5g of polyacrylate binder is added to obtain a flame retardant composition slurry. Step 3: 11g of aluminum oxide is added to the flame retardant composition slurry obtained in step 2, and stirred and dispersed to obtain a flame retardant slurry. Step 4: The flame retardant slurry in step 3 is coated on one side of a polyethylene (PE) base film with a thickness of 12 μm by a micro-concave roller coating process. After drying at 80°C, a flame retardant layer with a thickness of 10 μm is obtained. A 3 μm Al2O3 surface treatment layer is coated on the other side to obtain a diaphragm with a total thickness of 25 μm.
[0071] Preparation of positive electrode:
[0072] The positive electrode active material LiNi 0.9 Co 0.05 Mn0.05 O2 (NCM900), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully slurried in an N-methylpyrrolidone (NMP) solvent system in a weight ratio of NCM811: conductive carbon black: PVDF = 97.5:1.5:1.0, and then coated on a 12μm thick aluminum-coated current collector, dried, and roll-pressed to obtain a positive electrode sheet.
[0073] Preparation of negative electrode sheet:
[0074] The negative electrode active material silicon (SiOx, 0.5≤x≤1.5)-graphite composite (silicon accounts for 28wt%), conductive agent conductive carbon black, binder styrene-butadiene rubber SBR, thickener sodium carboxymethyl cellulose CMC-Na, and polyacrylic acid PAA are fully slurried in deionized water in a weight ratio of 95:2:1.5:1:0.5, coated on a 8μm thick copper current collector, dried, and roll-pressed to obtain a negative electrode sheet.
[0075] Preparation of electrolyte:
[0076] In a glove box filled with argon (H2O≤0.1ppm, O2≤0.1ppm), lithium salt LiPF6 and solvent EC / DEC / EMC (ethylene carbonate / diethyl carbonate / ethyl methyl carbonate) = 25 / 20 / 55 are mixed evenly in a certain proportion to prepare a 1M solution, and the lithium ion battery electrolyte in the embodiment is obtained after stirring evenly.
[0077] Preparation of lithium-ion batteries:
[0078] The positive electrode sheet, the separator and the negative electrode sheet are stacked to obtain a bare cell; the bare cell is placed in an aluminum-plastic film outer package, and the prepared electrolyte is injected after being fully dried. The battery is left at 45°C for 48 hours, formed in a high-temperature fixture (the formation conditions are: temperature 45°C, pressure 210kgf, 0.05C current charging to 4.25V and standing for 60min, then 0.1C charging to 4.25V, and then 0.2C discharging to 3.0V, and this is repeated three times) and secondary sealing, and then conventional capacity division is carried out.
[0079] Example 2
[0080] The method is basically the same as Example 1, except that the flame retardant layer in the diaphragm is prepared differently, as follows:
[0081] Preparation of diaphragm:
[0082] Step 1: The commercially available ammonium polyphosphate particles are ball-milled with a zirconium oxide ball mill, and then the ball-milled ammonium polyphosphate is dispersed in deionized water, centrifuged and vacuum dried to obtain ammonium polyphosphate powder. Step 2: 1.875g urea phosphate, 22.875g ammonium polyphosphate powder, 6.375g pentaerythritol, 6.375g melamine, 0.75g polyvinyl pyrrolidone, 0.2g sodium carboxymethyl cellulose and 0.05g sodium dodecyl sulfate are fully stirred and dispersed in water, and 4g polyacrylate binder is added to obtain a flame retardant composition slurry. Step 3: 7.5g aluminum oxide is added to the flame retardant composition slurry obtained in step 2, and stirred and dispersed to obtain a flame retardant slurry. Step 4: The flame retardant slurry in step 3 is coated on both sides of a PE base film with a thickness of 12 μm by a micro-concave roller coating process. After drying at 80°C, a flame retardant layer with a thickness of 10 μm is obtained to obtain a diaphragm with a total thickness of 32 μm.
[0083] Example 3
[0084] The method is basically the same as Example 1, except that the flame retardant layer in the diaphragm is prepared differently, as follows:
[0085] Preparation of diaphragm:
[0086] Step 1: The commercially available ammonium polyphosphate particles are ball-milled with a zirconium oxide ball mill, and then the ball-milled ammonium polyphosphate is dispersed in deionized water, centrifuged and vacuum dried to obtain ammonium polyphosphate powder. Step 2: 1.625g of diammonium phosphate, 21.125g of ammonium polyphosphate powder, 4.875g of tripentaerythritol, 4.875g of melamine, 0.75g of polyvinyl pyrrolidone, 0.2g of sodium carboxymethyl cellulose and 0.05g of sodium dodecyl sulfate are fully stirred and dispersed in water, and then 2.5g of polyacrylate binder is added to obtain a flame retardant composition slurry. Step 3: 9g of aluminum oxide is added to the flame retardant composition slurry obtained in step 2, and stirred and dispersed to obtain a flame retardant slurry. Step 4: The flame retardant slurry in step 3 is coated on both sides of a PE base film with a thickness of 12 μm by a micro-concave roller coating process. After drying at 80°C, a flame retardant layer with a thickness of 10 μm is obtained to obtain a diaphragm with a total thickness of 32 μm.
[0087] Example 4
[0088] The method is basically the same as Example 1, except that the flame retardant layer in the diaphragm is prepared differently, as follows:
[0089] Preparation of diaphragm:
[0090] Step 1: The commercially available ammonium polyphosphate particles are ball-milled with a zirconium oxide ball mill, and then the ball-milled ammonium polyphosphate is dispersed in deionized water, centrifuged and vacuum dried to obtain ammonium polyphosphate powder. Step 2: 1.425g urea phosphate, 16.53g ammonium polyphosphate powder, 5.13g dipentaerythritol, 5.415g melamine, 0.75g polyvinyl pyrrolidone, 0.2g sodium carboxymethyl cellulose and 0.05g sodium dodecyl sulfate are fully stirred and dispersed in water, and 2.5g polyacrylate binder is added to obtain a flame retardant composition slurry. Step 3: 18g aluminum oxide is added to the flame retardant composition slurry obtained in step 2, and stirred and dispersed to obtain a flame retardant slurry. Step 4: The flame retardant slurry in step 3 is coated on both sides of a PE base film with a thickness of 12 μm by a micro-concave roller coating process. After drying at 80°C, a flame retardant layer with a thickness of 10 μm is obtained to obtain a diaphragm with a total thickness of 32 μm.
[0091] Example 5
[0092] The method is basically the same as Example 1, except that the flame retardant layer in the diaphragm is prepared differently, as follows:
[0093] Preparation of diaphragm:
[0094] Step 1: The commercially available ammonium polyphosphate particles are ball-milled with a zirconium oxide ball mill, and then the ball-milled ammonium polyphosphate is dispersed in deionized water, centrifuged and vacuum dried to obtain ammonium polyphosphate powder. Step 2: 0.57g urea phosphate, 16.53g ammonium polyphosphate powder, 5.13g dipentaerythritol, 5.415g melamine, 0.75g polyvinyl pyrrolidone, 0.2g sodium carboxymethyl cellulose and 0.05g sodium dodecyl sulfate are fully stirred and dispersed in water, and 2.5g polyacrylate binder is added to obtain a flame retardant composition slurry. Step 3: 18g aluminum oxide is added to the flame retardant composition slurry obtained in step 2, and stirred and dispersed to obtain a flame retardant slurry. Step 4: The flame retardant slurry in step 3 is coated on both sides of a PE base film with a thickness of 12 μm by a micro-concave roller coating process. After drying at 80°C, a flame retardant layer with a thickness of 10 μm is obtained to obtain a diaphragm with a total thickness of 22 μm.
[0095] Example 6
[0096] The method is basically the same as Example 1, except that the flame retardant layer in the diaphragm is prepared differently, as follows:
[0097] Preparation of diaphragm:
[0098] Step 1: The commercially available phosphate particles are ball-milled with a zirconium oxide ball mill, and then the ball-milled ammonium polyphosphate is dispersed in deionized water, centrifuged and vacuum dried to obtain phosphate powder. Step 2: 1.2g diammonium hydrogen phosphate, 19.6g phosphate, 6.9g dipentaerythritol, 6.9g melamine, 0.75g polyvinyl pyrrolidone, 0.2g sodium carboxymethyl cellulose and 0.05g sodium dodecyl sulfate are fully stirred and dispersed in water, and 3.5g polyacrylate binder is added to obtain a flame retardant composition slurry. Step 3: 11g aluminum oxide is added to the flame retardant composition slurry obtained in step 2, and stirred and dispersed to obtain a flame retardant slurry. Step 4: The flame retardant slurry in step 3 is coated on one side of a PE base film with a thickness of 12 μm by a micro-concave roller coating process. After drying at 80°C, a flame retardant layer with a thickness of 5 μm is obtained. A 3 μm Al2O3 surface treatment layer is coated on the other side to obtain a diaphragm with a total thickness of 25 μm.
[0099] Example 7
[0100] The method is basically the same as Example 1, except that the flame retardant layer in the diaphragm is prepared differently, as follows:
[0101] Preparation of diaphragm:
[0102] Step 1: The commercially available phosphate particles are ball-milled with a zirconium oxide ball mill, and then the ball-milled ammonium polyphosphate is dispersed in deionized water, centrifuged and vacuum dried to obtain phosphate powder. Step 2: 0.38g of phosphoric acid and urea composition, 19.6g of phosphate, 6.9g of dipentaerythritol, 6.9g of melamine, 0.75g of polyvinyl pyrrolidone, 0.2g of sodium carboxymethyl cellulose and 0.05g of sodium dodecyl sulfate are fully stirred and dispersed in water, and then 3.5g of polyacrylate binder is added to obtain a flame retardant composition slurry. Step 3: 11g of aluminum oxide is added to the flame retardant composition slurry obtained in step 2, and stirred and dispersed to obtain a flame retardant slurry. Step 4: The flame retardant slurry in step 3 is coated on one side of a PE base film with a thickness of 12 μm by a micro-concave roller coating process. After drying at 80°C, a flame retardant layer with a thickness of 5 μm is obtained. A 3 μm Al2O3 surface treatment layer is coated on the other side to obtain a diaphragm with a total thickness of 25 μm.
[0103] Comparative Example 1
[0104] It is basically the same as Example 1, except that the separator is a commercially available 12 μm polyethylene PE-based film.
[0105] Comparative Example 2
[0106] It is basically the same as Example 1, except that the separator is: a 3 μm thick Al2O3 surface treatment layer is coated on both sides of a commercially available 12 μm polyethylene PE base film to obtain a 18 μm thick separator.
[0107] Comparative Example 3
[0108] The method is basically the same as Example 1, except that the flame retardant layer in the diaphragm is prepared differently, as follows:
[0109] Preparation of diaphragm:
[0110] Step 1: The commercially available ammonium polyphosphate particles are ball-milled with a zirconium oxide ball mill, and then the ball-milled ammonium polyphosphate is dispersed in deionized water, centrifuged and vacuum dried to obtain ammonium polyphosphate powder. Step 2: 21.125g of ammonium polyphosphate powder, 5.525g of melamine, 5.85g of tripentaerythritol, 0.75g of polyvinyl pyrrolidone, 0.2g of sodium carboxymethyl cellulose and 0.05g of sodium dodecyl sulfate are fully stirred and dispersed in water, and then 2.5g of polyacrylate binder is added to obtain a flame retardant composition slurry. Step 3: 9g of aluminum oxide is added to the flame retardant composition slurry obtained in step 2, and stirred and dispersed to obtain a flame retardant slurry. Step 4: The flame retardant slurry in step 3 is coated on both sides of a PE base film with a thickness of 12μm by a micro-concave roller coating process, and after drying at 80°C, a flame retardant layer with a single-side thickness of 10μm is obtained to obtain a diaphragm with a thickness of 32μm.
[0111] Test method
[0112] 1. Diaphragm infiltration electrolyte combustion test:
[0113] The separator was cut into a size of 5×5 cm and immersed in an electrolyte with a molar ratio of EC:DMC:DEC (1:1:1). The separator immersed in the electrolyte was ignited and the burning time (SET) of the separator was recorded.
[0114] 2. Heat shrinkage test:
[0115] The area of the 5×5 cm diaphragm is recorded as S1. The diaphragm is placed in an oven at 150° C. for 1 hour and the area S2 of the diaphragm is recorded. The heat shrinkage ratio = (S1-S2) / S1.
[0116] 3. Diaphragm thickness test:
[0117] Cut the membrane into 10×10cm size, place it in a 150℃ oven for 1h, record the thickness D1 of the membrane center before baking and the thickness D2 after baking, and calculate the thickness difference ΔD before and after baking = D2-D1. The larger the thickness difference, the greater the thickness growth after baking, and the better the membrane expansion effect.
[0118] 4. Acupuncture test:
[0119] Use a 1mm diameter high temperature resistant steel needle with a taper of 30° to penetrate the battery at a speed of 2mm / s, perpendicular to the center of the large surface.
[0120] The diaphragms or batteries obtained from Examples 1 to 7 and Comparative Examples 1 to 3 were subjected to diaphragm impregnation electrolyte combustion test, diaphragm heat shrinkage test, diaphragm test and battery puncture test, respectively. The test results are shown in Table 1, where the pass status of the puncture test represents the number of times the puncture test was passed in 5 times, for example, 1 / 5 represents one pass in 5 times the puncture test.
[0121] Table 1
[0122]
[0123] It can be seen from Examples 1 to 7 and Comparative Examples 1 to 3 that when the flame retardant layer of the diaphragm contains the first component, the flame retardant layer of the diaphragm can form an expanded carbon layer at 150°C, and obtain excellent performance in the needle puncture test, which effectively improves the needle puncture safety of the battery cell using the diaphragm. Therefore, when the diaphragm is used in a secondary battery, the secondary battery has higher safety performance.
[0124] As can be seen from Comparative Examples 1 to 2, the diaphragm without a flame retardant layer has a significantly increased burning time (SET), a high thermal shrinkage rate, and a poor safety performance. As can be seen from Comparative Example 3, when the flame retardant layer of the diaphragm contains the second component, the third component, and the fourth component, but the first component of the present invention is not added, the passing rate of the diaphragm under the acupuncture test is still poor, and the acupuncture safety of the battery cell using the diaphragm is also poor.
[0125] like Figure 3 As shown, when the separator according to the present invention is punctured by a needle, the flame retardant layer can expand at a relatively low temperature (eg, 150° C.) to produce an expanded carbon layer, thereby effectively preventing the battery cell from burning.
[0126] Although some exemplary embodiments of the present invention have been illustrated and described, the present invention is not limited to the disclosed embodiments. On the contrary, those of ordinary skill in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present invention as described in the appended claims, and these modifications and changes also fall within the scope of protection of the present invention.
Claims
1. A diaphragm, characterized in that: include: Basement membrane; A flame retardant layer is arranged on the base film, the flame retardant layer includes a flame retardant composition, the flame retardant composition includes a first component, the first component includes: at least one of (i) urea phosphate, (ii) a mixture of phosphoric acid and urea, (iii) diammonium phosphate and (iv) diammonium hydrogen phosphate.
2. The diaphragm according to claim 1, characterized in that The flame retardant composition further comprises: a second component, the second component comprising at least one of ammonium polyphosphate, a phosphate ester, sodium tetraborate, and ammonium borate; A third component, the third component comprising at least one of pentaerythritol, dipentaerythritol, tripentaerythritol, phenolic resin, polyamide, tetramethylenetetraol, cyclohexanehexol, starch, maltose, piperazine pyrophosphate and triazine compounds; The fourth component includes at least one of melamine, urea, dicyandiamide, urea-formaldehyde resin and polyurea.
3. The diaphragm according to claim 2, characterized in that The first component comprises at least one of urea phosphate, diammonium phosphate and diammonium hydrogen phosphate; and / or The base film has a thickness of 5 μm to 20 μm; and / or The flame retardant layer has a thickness of 1 μm to 20 μm.
4. The diaphragm according to claim 2, characterized in that Based on the total mass of the flame retardant layer, the mass percentage of the flame retardant composition is 57% to 93%; and / or Based on the total mass of the flame retardant composition, the mass percentage of the first component is 2% to 5%; and / or Based on the total mass of the flame retardant composition, the mass percentage of the second component is 55% to 68%, the mass percentage of the third component is 15% to 20%, and the mass percentage of the fourth component is 15% to 20%.
5. The diaphragm according to any one of claims 1 to 4, characterized in that: The flame retardant layer further comprises: first inorganic particles, the first inorganic particles comprising at least one of aluminum oxide, boehmite, magnesium hydroxide, aluminum hydroxide, garnet and silicon dioxide; based on the total mass of the flame retardant layer, the mass percentage of the first inorganic particles is 5% to 40%; and / or A first binder, wherein the first binder comprises at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylate, polyvinyl alcohol and polyvinylidene fluoride; based on the total mass of the flame retardant layer, the mass percentage of the first binder is 2% to 10%.
6. The diaphragm according to claim 5, characterized in that The flame retardant layer further comprises: An auxiliary agent, wherein the auxiliary agent comprises at least one of a dispersant, a thickener and a wetting agent; Wherein, the dispersant includes at least one of polyacrylate, sodium polyacrylate, ammonium polyacrylate, sodium hexametaphosphate, polyethylene glycol, polyethylene glycol ether and polyvinyl pyrrolidone, the thickener includes at least one of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, gelatin and sodium alginate, and the wetting agent includes at least one of siloxane, polyether-modified polydimethylsiloxane, sodium perfluoroalkyl sulfonate, polyethylene oxide, sodium dodecyl sulfate and sodium dodecyl sulfonate; Based on the total mass of the flame retardant layer, the mass percentage of the dispersant is 1% to 2%, the mass percentage of the thickener is 0.3% to 1%, and the mass percentage of the wetting agent is 0.05% to 0.2%.
7. The diaphragm according to claim 1, characterized in that The base film comprises at least one of polyethylene, polypropylene, a polypropylene / polyethylene / polypropylene three-layer composite film, polyethylene terephthalate, polyimide and aramid; and / or The flame retardant layer is disposed on one side surface of the base film and the surface treatment layer is disposed on the other side surface opposite thereto, or the flame retardant layer is disposed on both sides of the base film opposite thereto; wherein the surface treatment layer comprises at least one of a polymer, a second inorganic particle and a combination of a second binder; the polymer comprises at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene); the combination of the second inorganic particle and the second binder In the invention, the second inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate, and the second binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
8. A method for preparing a diaphragm, characterized in that: include: A base film and a flame retardant layer slurry are provided, wherein the flame retardant layer slurry comprises a flame retardant composition, wherein the flame retardant composition comprises a first component, wherein the first component comprises at least one of (i) urea phosphate, (ii) a mixture of phosphoric acid and urea, (iii) diammonium phosphate, and (iv) diammonium hydrogen phosphate; The flame retardant layer slurry is formed on the base film, and the separator is formed by a drying process.
9. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a separator according to any one of claims 1 to 7 or a separator formed by the preparation method according to claim 8.
10. A device, characterized in that: The device comprises the secondary battery according to claim 9.